IMPLEMENTASI DATA MINING DENGAN METODE APRIORI UNTUK REKOMENDASI SUKU CADANG PONSEL DAN PREDIKSI PENJUALAN PRODUK SETIAP PELANGGAN - Hanven Pradana; Viny Christanti Mawardi; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Application of cell phone parts recommendations and product sales predictions for each customer for Brader Parts is an application that is made aiming to provide predictions of each customer's buying habits as well as recommendations in selecting what items are most salable to sell and most sought after. This application was designed using the ASP.Net programming language. Method of Calculating application using Apriori. The design of the application uses the System Development Life Cycle. The test results are performed using the User Acceptance Test method and user satisfaction testing. With this application, it is expected that the process of consideration and selection of goods at the Brader Parts company can be helped.